2016
DOI: 10.1039/c6cp01423b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of CuTPP and CuTPP(F) complexes. A combined experimental and theoretical study I

Abstract: Copper complexes of tetraphenylporphyrin (H2TPP) and tetrakis(pentafluorophenyl)porphyrin (H2TPP(F)) deposited as thin films on Au(111) have been studied experimentally and theoretically. Core level emissions from C 1s, N 1s, F 1s and Cu 2p as well as valence states of CuTPP and CuTPP(F) have been investigated using surface photoelectron spectroscopy. The interpretation of experimental results has been guided by theoretical calculations carried out on isolated species in the habit of the density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Experimental and theoretical studies[16b], [16c], [16d], carried out in our group on several Cu II complexes confirmed the legitimacy of exploiting the Cu II L 3 ‐edge position to estimate the ligand‐field strength exerted on the Cu II center. On the other hand, TD‐DFT SO‐ZORA TDA calculations on Cu II complexes having ligands with [PcCu, TPPCu, TPP(F)Cu, (acac) 2 Cu[16d]] or without ([CuCl 4 ] 2– ,[16d] the oxidized blue copper site in plastocyanin[16d]) low‐lying π* orbitals revealed the possibility of a Cu–L covalency underestimation if the Cu II L 3 ‐edge intensity of the former complexes is used as a gauge.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Experimental and theoretical studies[16b], [16c], [16d], carried out in our group on several Cu II complexes confirmed the legitimacy of exploiting the Cu II L 3 ‐edge position to estimate the ligand‐field strength exerted on the Cu II center. On the other hand, TD‐DFT SO‐ZORA TDA calculations on Cu II complexes having ligands with [PcCu, TPPCu, TPP(F)Cu, (acac) 2 Cu[16d]] or without ([CuCl 4 ] 2– ,[16d] the oxidized blue copper site in plastocyanin[16d]) low‐lying π* orbitals revealed the possibility of a Cu–L covalency underestimation if the Cu II L 3 ‐edge intensity of the former complexes is used as a gauge.…”
Section: Resultsmentioning
confidence: 74%
“…Cu II ions have a 3d 9 electronic configuration and, in the D 4 h Cu II complexes considered herein, the fivefold degeneracy of the 3d AOs is lifted by the square planar ligand field (see Figure , panels a and b); four low‐lying, double occupied MOs (DOMOs) of symmetry a 1g ( z 2 ), b 2g ( xy ) and e g ( xz, yz ), as well as a singly occupied MO (SOMO) of symmetry b 1g ( x 2 – y 2 ) are then generated , . All the Cu II 3d‐based MOs are Cu–N Py[55] antibonding in nature (see Figure );[16b], , the rather small and very similar Cu–N Py NM I in PcCu (0.26, see Table ) and TPPCu/TPP(F)Cu (0.27, see Table ) are therefore not particularly surprising. If we add that the Cu and N Py Hirshfeld gross atomic charges ( H Q Cu and H Q N , respectively) in PcCu, TPPCu and TPP(F)Cu amounts to 0.42, 0.40, 0.42 and –0.15 respectively (see Table ), it can be assessed with some confidence that ionic contributions play an important role in the Cu–N Py bonding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations